(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This article discusses the need for intervention in a reinforced concrete structure due to its need to adapt to his new role. This is the evaluation of structural conditions of a place that, in future, would be the Fun House CLUB HOG, where two mezzanines would be installed to increase its service area. Then, an assessment of the influence of these mezzanines in bearing capacity of the existing concrete structure was made, and the best option was chosen.In addition, the structural reinforcement necessary was calculated. Finally, the structural design of this deployment was carried out.